Uji Reliabilitas Instrumen Kualitas Hidup pada Penderita Kanker Payudara Reability Test on The Instrument of Quality of Life For Breast Cancer Patients - Djuminten Siswanto Agus Wilopo Kunta Setiaji (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Background: Breast cancer can influence the quality of patient’s life. A measurement of quality of life (QOL) is important to evaluate the health services and the continuity of patient life. The Quality of Life Instrument (Quality of Life Breast Cancer Scale) by Ferrell, et al (1995) which has been translated into Indonesian as The Quality of Life Breast Cancer Instrument has not been tested its reliability.Objective: To know the instrument’s reliability and measuring agreement rating of breast cancer patient’s life quality between two raters.Method: This was an observational study using a cross-sectional study design. The subjects were 50 women with stage II-III of breast cancer at Sardjito Hospital selected using an accidental sampling technique. Data was collected through interviews using the QOL instrument guideline. Each subject was interviewed twice by nurse and midwife with 2-14 days difference between the interviews. The data were analyzed with Univariate, and Bivariate with Coefficient Kappa analysis, Intraclass Coefficient Correlation analysis, and alfa Cronbach Coefficient analysis.Results: The Kappa analysis to 46 items of quality of life questions done by nurse and midwife resulted in “good” and “very good” category. The lowest result was k=0.63 and the highest result was k=1.00. The lowest result of coefficient alpha analysis was r=0.63/0.63 while the highest was r=0.88/0.87. The lowest intraclass coefficient was r=0.93 while the highest was r=0.99.Conclusion: The quality of life breast cancer instrument could likely be adapted for breast cancer patients in Indonesia.Keywords: reliability, instrument, quality of life, breast cancer, Sardjito.